2017
DOI: 10.17554/j.issn.2409-5680.2017.03.60
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ophthalmic Disorders and Congenital Cardiac Disease in Children with Down Syndrome

Abstract: The most frequent ocular anomalies found were myopia in 62 eyes, hypermetropia in 58 eyes and astigmatism in 54 eyes. In the DIA subjects hypermetropia is prevalent, and in those with DIV and/ or AVSD the other three anomalies (hypermetropia, myopia and astigmatism) are more or less equally frequent. CONCLUSIONS: Our study confirms the frequent association between congenital cardiac diseases and ocular anomalies, above all refractive defects, in DS patients, and draws attention to the need for early ophthalmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A study in Italy has reported significant association between ocular anomalies and CHD. [19] Although, majority of the patients seen were asymptomatic, those who had detectable cardiac murmurs eventually turned out positive for CHD. However, some did not also have any murmur and were diagnosed with complex defects.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Italy has reported significant association between ocular anomalies and CHD. [19] Although, majority of the patients seen were asymptomatic, those who had detectable cardiac murmurs eventually turned out positive for CHD. However, some did not also have any murmur and were diagnosed with complex defects.…”
Section: Discussionmentioning
confidence: 99%